Ultra-wideband signal generator based on cross gain modulation effect in a distributed feedback laser. (October 2016) - Chen, Dalei; Wang, Rong; Xiang, Peng; Pu, Tao; Fang, Tao; Li, Yuandong; Su, Yang; Zheng, Jiling; Huang, Long; Zhu, Huatao; Huang, Jie
Abstract: In this paper, a novel scheme to generate ultra-wideband (UWB) signals based on cross-gain modulation (XGM) effect in a DFB laser is proposed and experimentally demonstrated, and the modulation and transmission of the UWB signals are also experimentally investigated. In the proposed system, a gain-switched laser (GSL) is used as master laser (ML) and the optical pulses from the ML are optically injected into a DFB laser, which is used as slave laser (SL). By proper system configuration, UWB monocycle, doublet or triplet UWB signals can be generated after the balanced photodiode (BPD) detection. Besides, other modulation formats can also be realized, such as on-off keying (OOK) and pulse amplitude modulation (PAM) by properly modulating the ML optical pulses. Finally, fiber transmission of the modulated UWB signals is experimentally investigated, and it is shown that the UWB signals can be well maintained after 40 km optical fiber transmission. Highlights: A novel approach to generate the UWB signal is proposed. UWB monocycle, doublet and triplet UWB signals are generated. OOK and PAM of the generated UWB signals are realized. Our system is fast enough for UWB applications. The transmission of the modulated UWB signals is demonstrated.